Comparative Analysis Of Conventional Method With Activity Based Costing In PT Mulia Sejati Gallery - Erena, Irma Nadia; Gani, Engelwati (Journal the Winners: Economics, Business, Management, and Information System Journal, 2016)
The goal of this research was to provide readers the information about the calculation methods, both traditional and activity-based costing in the application of the cost of production. The method used in this research was the qualitative method. The analysis was done by calculating the amount of the production cost using the traditional system and the magnitude of the production cost when using the activity-based costing system. The amount of each acquisition was then performed into data analysis. The results achieved are massive distortion between the calculations using traditional systems and activity based costing system. The conclusions of the whole thesis are activity-based costing system is considered more relevant than traditional systems that are currently used by the company.